2019
DOI: 10.1002/ijc.32109
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric characteristics, physical activity and risk of hematological malignancies: A systematic review and meta‐analysis of cohort studies

Abstract: Overweight/obesity, adult attained height and physical activity are possible risk factors for hematological malignancies. This meta‐analysis aims to evaluate the associations between these factors and hematological cancer risk in adults. Eligible cohort studies were sought in PubMed up to May 31, 2016; overall, 44 studies were included in the present analyses. Pooled relative risk estimates were calculated using random‐effects models; separate analyses were conducted for non‐Hodgkin lymphoma (NHL) and subtypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 95 publications
(176 reference statements)
2
26
1
Order By: Relevance
“…This meta-analysis expands on prior work [5,10,14] by incorporating two case-control [15,16] and two cohort studies [17,18] with 1432 additional lymphoma cases that have since been published, increasing case sample size by approximately 12%. In addition, within previous efforts [10] the outcome key words of "(lymphoma OR Hodgkin)" were likely satisfactory, however the exposure keywords may have missed studies examining specific forms of activity leading to incomplete evaluation which require further examination in subgroup or sensitivity analyses.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…This meta-analysis expands on prior work [5,10,14] by incorporating two case-control [15,16] and two cohort studies [17,18] with 1432 additional lymphoma cases that have since been published, increasing case sample size by approximately 12%. In addition, within previous efforts [10] the outcome key words of "(lymphoma OR Hodgkin)" were likely satisfactory, however the exposure keywords may have missed studies examining specific forms of activity leading to incomplete evaluation which require further examination in subgroup or sensitivity analyses.…”
Section: Introductionmentioning
confidence: 87%
“…In addition to new oncologic therapies, further research is needed to direct disease prevention, specifically modifiable risk factors, such as physical activity. Prior metaanalyses demonstrated a relationship between obesity and lymphoma incidence in a dose-dependent manner (obesity vs. overweight vs. normal weight) [5][6][7]; however, it remains unclear if there is an association between physical activity and lymphoma independent of body mass index (BMI) [8]. Additionally, BMI does not always reflect obesity or inactivity, therefore an alternate metric was considered.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of BCL has been associated with lifestyle, viral, and environmental factors 13 , 14 . A large study from the International Lymphoma Epidemiology Consortium (InterLymph) showed several risk/protective factors for Non-Hodgkin lymphoma subtypes 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The clinical implications of body habitus based on anthropometric measures have been intensively studied in various cancers (14)(15)(16)(17). However, anthropometric measures such as BMI, waist circumference, or waist:hip ratio have limitations, and do not fully reflect muscle and fat mass (4).…”
Section: Discussionmentioning
confidence: 99%